Review of thermal neutron scintillators: Evaluation metrics and future prospects for demanding applications - G. Jeff Sykora; Sarah E. Mann; Giacomo Mauri; Erik M. Schooneveld; Nigel J. Rhodes (Optical Materials: X)
Neutron applications are progressing rapidly, requiring detectors to meet increasingly rigorous criteria. Specifications such as high neutron counting rates, fast timing resolution and low background have a significant impact on choice of scintillator and how scintillators are evaluated. This work considers detector requirements for neutron scattering instruments that are becoming more stringent as the sources and scattering technologies continue to improve. Meanwhile, both prominent scintillators used for neutron scattering detectors, ZnS:Ag/6LiF and GS-glass, remain stagnant. While these scintillators have been suitable for many years, they are becoming a limiting factor for neutron scattering instruments. ZnS:Ag is inhibiting count rate capability and GS-glass is too gamma sensitive so alternatives need to be found. A brief explanation of neutron scattering, its detector requirements and how those relate to scintillator properties will be discussed. Furthermore, this work explains how standard characterization methods and reporting of scintillation properties are not entirely suitable for high count rate, low background applications like neutron scattering. As a result, modifications to characterization of gamma discrimination, light output, and decay kinetics are suggested. Additional steps are suggested including neutron activation and a more appropriate assessment of count rate capability. A non-exhaustive set of 6Li containing neutron sensitive scintillators including ZnS:Ag/6LiF, GS20 glass, ZnO:Zn/6LiF, Cs6LiYCl:Ce, 6LiI:Eu, 6LiI:Ce, 6LiCaAlF:Eu, LiCaAlF:Ce, transparent rubber sheet (TRUST) 6LiCaAlF:Eu, TRUST 6LiCaAlF:Eu with added fluorophore and EJ-270 (6Li containing plastic) are reviewed and studied from this different perspective. Finally, new scintillator developments relevant to high count rate, low background applications are discussed.